2009
DOI: 10.1097/hjh.0b013e32832d4692
|View full text |Cite
|
Sign up to set email alerts
|

Management of antihypertensive drugs in three European countries

Abstract: Management of hypertension is unsatisfactory worldwide due to a very high rate of treatment discontinuation or insufficient use of proper treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…This answers negatively the question whether using combination treatment as first step may be associated also with a better long-term BP control, possibly because two advantages of the combination, that is better BP control and tolerance profile, are major determinants of long-term compliance to treatment [18,19]. It should be emphasized, however, that this question may be more properly addressed by studies of a longer duration performed in the context of real life treatment [8,[20][21][22] because the close patient follow-up typical of clinical trials may be associated with an overall high patients' compliance which makes differences between treatment strategies more difficult to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This answers negatively the question whether using combination treatment as first step may be associated also with a better long-term BP control, possibly because two advantages of the combination, that is better BP control and tolerance profile, are major determinants of long-term compliance to treatment [18,19]. It should be emphasized, however, that this question may be more properly addressed by studies of a longer duration performed in the context of real life treatment [8,[20][21][22] because the close patient follow-up typical of clinical trials may be associated with an overall high patients' compliance which makes differences between treatment strategies more difficult to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment discontinuation, as shown by a national study based on the Swedish Prescribed Drug Register, is about 50% of the Swedish population who receive any hypertension drugs. This might contribute to poor hypertension control (34). Johnell et al identified low social participation as potential contributing factor contributing to low adherence with antihypertensive medication among the population in a southern county of Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…W e have previously shown that in the population of Lombardy, a region with more than 10 million residents located in Northern Italy, adherence to antihypertensive drug treatment is extremely low [1][2][3]. The data were derived from the regional healthcare utilization database, which provides pharmacy-dispensing information.…”
Section: Introductionmentioning
confidence: 99%